University Dropout Problems and Solutions - Giuseppe Bertola (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Frequent non-completion in optional education can be e cient if dropouts optimally exercise an option rationally foreseen by previous enrollment choices. This paper shows that in educational opportunities and groups of students where enrollment resolves more pronounced individual uncertainty both enrollment and dropout are higher, with ambiguous degree completion eects, and educational outcomes are unambiguously better in expectation and on average.
Keywords: I22; I28; 330; option value; higher education